2012
DOI: 10.1093/rheumatology/kes226
|View full text |Cite
|
Sign up to set email alerts
|

Joint and tendon involvement in systemic lupus erythematosus: an ultrasound study of hands and wrists in 108 patients

Abstract: The picture of musculoskeletal US in SLE depends on arthropathy subtype and disease activity. US examination could be a valid and reliable tool to monitor musculoskeletal features and therapeutic outcomes in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
6
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 31 publications
5
93
6
3
Order By: Relevance
“…Secondly, joint deformities are observed in up to 35% of patients and appear to be associated with difficulties in performing daily activities and may require surgery [10]. Finally, ultrasound studies have shown an unexpected high prevalence of synovitis, tenosynovitis and erosions also in SLE patients (Table 4) [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, joint deformities are observed in up to 35% of patients and appear to be associated with difficulties in performing daily activities and may require surgery [10]. Finally, ultrasound studies have shown an unexpected high prevalence of synovitis, tenosynovitis and erosions also in SLE patients (Table 4) [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The wrist and 2nd-5th metacarpophalangeal joints (MCP) were the target joints and the study was performed with a low-field extremity dedicated 0.2 T instrument (C-scan, Esaote Biomedica, Genoa, Italy); coronal and axial T1-weighted gradient-echo images and coronal STIR images were acquired. The images acquired were scored according to the RAMRIS scoring system for RA by a trained radiologist unaware of the clinical picture and diagnosis [13,14]. Briefly, the erosions were scored from 0 to 10 according to the proportion (in increments of 10%) of bone involved.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The details of some of these studies have been reviewed elsewhere, 10 but all studies noted a higher than expected prevalence of synovitis, tenosynovitis and erosions than was estimated from clinical examination. The presence of erosions can obscure the boundary between SLE and rheumatoid disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the application of power Doppler allows to detect pathologically increased hematic perfusion, indicating an active synovitis. The studies conducted so far on SLE patients demonstrated the frequent detection of inflammatory signs in the radiocarpal joint (RC), followed by the metacarpophalangeal (MCP) and proximal-interphalangeal (PIP) joints [17][18][19]. Recently, we analyzed the involvement of metatarsophalangeal joints in a cohort of SLE patients, identifying a significantly higher frequency of inflammatory modifications compared with wrist, MCP and PIP joints [20].…”
Section: Joint Involvementmentioning
confidence: 99%